Prostaglandin E2 Signals Through E Prostanoid Receptor 2 to Inhibit Mitochondrial Superoxide Formation and the Ensuing Downstream Cytotoxic and Genotoxic Effects Induced by Arsenite - Liana Cerioni; Andrea Guidarelli; Mara Fiorani; Orazio Cantoni (Frontiers Media S.A., 2019)
We investigated the effects of prostaglandin E2 (PGE2), an important inflammatory lipid mediator, on the cytotoxicity-genotoxicity induced by arsenite. With the use of a toxicity paradigm in which the metalloid uniquely induces mitochondrial superoxide (mitoO2−.) formation, PGE2 promoted conditions favoring the cytosolic accumulation of Bad and Bax and abolished mitochondrial permeability transition (MPT) and the ensuing lethal response through an E prostanoid receptor 2/adenylyl cyclase/protein kinase A (PKA) dependent signaling. It was, however, interesting to observe that, under the same conditions, PGE2 also abolished the DNA-damaging effects of arsenite and that this response was associated with an unexpected suppression of mitoO2−. formation. We conclude that PGE2 promotes PKA-dependent inhibition of mitoO2−. formation, thereby blunting the downstream responses mediated by these species, leading to DNA strand scission and MPT-dependent apoptosis. These findings are therefore consistent with the possibility that, in cells responding to arsenite with mitoO2−. formation, PGE2 fails to enhance-but rather decreases-the risk of neoplastic transformation associated with genotoxic events.